Desecularization of the World Community as Tension Source in the International Relations and World Politics - I. V. SLEDZEVSKIY (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2018)
Article is devoted to a role of world religions in the modern international relations and world politics. The phenomenon of world religious revival, his connection with globalization processes, formation of the multi-polar, polycivilization world is investigated. A research objective is the analysis of tendencies of a desecularization of the world community, the reasons and possible consequences of this process in global measurement. Article includes Introduction, three analytical sections and the Conclusion. In Introduction the phenomenon of world religious revival and approaches to his studying is presented. It is asked about a desecularization of the world community as a possible subject of the new direction of the international political researches – the international religious studies. The thesis about crisis of secular bases of modern political system of the world is proved in the first section. Revision of bases of a world order and standards of belonging to the world community from positions of the reviving religious fundamentalism, the cultural and political and social and economic bases of this process are considered. In the second section the role in a desecularization of the world community of political Islam (Islamism) is analyzed. It is noted that the greatest danger of politicization of Islam consists in emergence of difficult surmountable civilization break in the world community between the Western world (still confident in universality of the values) and the world of Islam. In the third section the possibilities of prevention of disintegration of the existing system of the international relations and collision of the cultural worlds are considered. The main attention is paid to processes of a global political institutionalization of such dialogue and its justification in the concept of global ethics – purposeful coordination and gradual connection of the basic moral and ethical values concluded in great religious and cultural traditions of the world. In the final section of article the conclusion is drawn that process of an institutionalization of civilization dialogue (civilization communication) it isn’t finished yet and didn’t become irreversible.